EMPLOYEE CAREER DEVELOPMENT AND ATTAINMENT OF BALANCE SCORECARD TARGETS: A CASE STUDY OF NATIONAL HOSPITAL INSURANCE FUND - Kamuti, Charles Mwangangi; Linge, Dr.Kavoo (Journal of Human Resource and Leadership, 2017)
Purpose: The purpose of this study was to investigate the effect of employee career development to the achievement of Balanced Scorecard (BSC) targets in the National Hospital Insurance Fund (NHIF). Materials and methods: The research design was a descriptive case study in nature focusing on NHIF. The population of the study was 1360 staff of NHIF. Stratified random sampling technique was used to select a sample of (136) respondents. Data was collected using a structured questionnaire. Data was coded and entered into Statistical Package for Social Sciences (SPSS). The data was then analyzed in terms of descriptive statistics like frequencies and percentages. Inferential statistics were computed using the Pearson Correlation Analysis. The results were presented in figures and tables. Results: The study concludes that training efforts at NHIF were low, employee development efforts were lowly emphasized at NHIF, and career guidance efforts were lowly emphasized at NHIF. It can also be concluded that performance resulting from training was low. It was also possible to conclude that training had a positive correlation with the effect of training on achieving balance scorecard targets. The study concludes that employee development scores at NHIF were low. In addition, the study concluded that the effect of employee development on attainment of balance score card was low. Overall it was possible to conclude that career guidance efforts were lowly rated indicating that the management of NHIF does not invest in career guidance. It was also possible to conclude that the effect of career guidance on achievement of balance score card targets was poorly rated. Recommendations: The study recommended that training be emphasized at NHIF as it has an effect on the overall achievement of balance scorecard targets, that the organization needs to emphasize and encourage self or employee development by providing opportunities to employees to improve their knowledge, awareness, and develop their talents and that the organization needs to emphasize and support career guidance and mentoring as this will help improve employees self-esteem and job satisfaction.